ANALYSIS OF STUDENT RESPONSES TO LEARNING MODELS PROBLEM SOLVING ON PLANT TISSUE MATERIAL - Wardana, Siti (Jurnal Biologi Sains dan Kependidikan, 2024)
The teaching and learning process occurs because of the interaction between teachers, students and the environment as a source of learning. This research was conducted in November 2020. The purpose of this research is to describe students' responses to the Problem Solving learning model on plant tissue material. The research method uses a survey method. The research subjects were biology teachers who teach in grade XI and grade XI students. The research instruments were questionnaires and interviews. Data was analyzed by percentage. The results of the analysis of student responses to the biology learning model with plant tissue material showed that 61.87% of students responded positively. While 38.13 students responded negatively. The conclusion of this study is that the Problem Solving learning model can be very effective, However, the results depend on how this model is implemented and how prepared students are to follow the learning process.